PENGGUNAAN AIR TEBU YANG DIKOMBINASIKAN DENGAN KUNING TELUR SEBAGAI PENGENCER SEMEN SAPI BALI - Bardan Bardan; Feradis Feradis; Triani Adelina (State Islamic University of Sultan Syarif Kasim Riau, 2009)
Research on utilization sugar cane water combined with egg yolk as Bali bull semen extenMr have been implemented. Research was conducted to determine the level ofutilization ofsugar cane water as semen exten r combined with egg yolk on the quality ofBali bull semen. Variable observed in this study were the percentage ofmotility, the percentage of live count and intact plasma membrane of sperm. Based on the Complete Random Design (RAL) with ix treatments and three replications. Treatment A = skim milk extender (control), B = 10% sugar cane water extender, C